2012
DOI: 10.1200/jco.2011.36.7136
|View full text |Cite
|
Sign up to set email alerts
|

Updated Analysis of SWOG-Directed Intergroup Study 0116: A Phase III Trial of Adjuvant Radiochemotherapy Versus Observation After Curative Gastric Cancer Resection

Abstract: Intergroup 0116 (INT-0116) demonstrates strong persistent benefit from adjuvant radiochemotherapy. Toxicities, including second malignancies, appear acceptable, given the magnitude of RFS and OS improvement. LRF reduction may account for the majority of overall relapse reduction. Adjuvant radiochemotherapy remains a rational standard therapy for curatively resected gastric cancer with primaries T3 or greater and/or positive nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
535
3
22

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 712 publications
(588 citation statements)
references
References 43 publications
18
535
3
22
Order By: Relevance
“…Standard treatments for locally advanced gastric cancer differ among various regions: surgery followed by adjuvant chemoradiotherapy in the USA [2], pre-and postoperative chemotherapy in European countries [3], and postoperative chemotherapy in Asian countries [4,5]. Preoperative chemotherapy is a part of the standard treatment used in Europe and has been evaluated in many clinical trials in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Standard treatments for locally advanced gastric cancer differ among various regions: surgery followed by adjuvant chemoradiotherapy in the USA [2], pre-and postoperative chemotherapy in European countries [3], and postoperative chemotherapy in Asian countries [4,5]. Preoperative chemotherapy is a part of the standard treatment used in Europe and has been evaluated in many clinical trials in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…This trial showed an improvement in survival in patients who received adjuvant chemoradiotherapy, with 3-year OS rates of 50 % in the chemoradiotherapy group compared to 41 % in patients treated with surgery alone [9]. An update demonstrated that the benefit from chemoradiotherapy has persisted after more than 10 years of follow-up, with hazard ratios for overall survival of 1.32 (95 % CI, 1.10-1.6; P = 0.0046) and for relapse-free survival of 1.51 (95 % CI, 1.25-1.83; P = 0.001) [20]. Approximately 80 % of patients in INT-0116 had gastric cancer; the remaining 20 % were junctional tumors.…”
Section: Adjuvant Chemoradiotherapy: Optimal If High Risk Of Residualmentioning
confidence: 96%
“…Si sabemos que, estudios clínicos clásicos han demostrado, con dosis de 45-50 Gy se puede controlar el 90% de la enfermedad subclínica 8,9 , y esto en teoría aumenta al combinar quimioterapia en dosis radiosensibilizante. No nos es extraño que el uso de Radioquimioterapia adyuvante ha disminuido las fallas locorregionales y mejorado la sobrevida tanto en estudios institucionales chilenas 10 como internacionales 11 , y a la vez comprobado en randomizados multicéntricos internacionales 12,13 , y comprobado en metanálisis 14,15 . Nos pareció de interés investigar los resultados obtenidos con el uso de estas terapias en nuestro centro, tratados con Radioterapia (RT) y Quimioterapia (QT) adyuvante tal como asi lo indica el estándar mundial.…”
unclassified